2012
DOI: 10.1111/j.1468-5906.2012.01637.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Attitudes Toward Muslim Students Among Flemish Teachers: A Research Note

Abstract: Muslims are now the second largest religious group in almost all Western countries and a large majority of Muslim citizens are children who attend schools. However teachers' attitudes regarding the education of Muslim students are largely ignored by educational researchers. In this study, we investigate the determinants of teachers' attitudes among Flemish (Belgian) teachers (N = 620). Regression analysis has revealed that female teachers, Muslim teachers, younger teachers, and teachers with a four-year colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 33 publications
1
33
1
Order By: Relevance
“…Our results support the claims of previous research literature that in comparison to males, female teachers might have a more pedagogical orientation, be more focused on the personal development of students, and consider teaching immigrant students to be more enriching (Beijaard, Verloop, and Vermunt ; Talib ). However, we did not find Finnish teachers’ attitudes toward Muslim students to be as gender related as did Agirdag, Loobuyck, and van Houtte () in their study of Flemish teachers. Even though attitudes to minorities have often been found to be gender related, in Finland this link seems to be weaker (see also Ketola ).…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…Our results support the claims of previous research literature that in comparison to males, female teachers might have a more pedagogical orientation, be more focused on the personal development of students, and consider teaching immigrant students to be more enriching (Beijaard, Verloop, and Vermunt ; Talib ). However, we did not find Finnish teachers’ attitudes toward Muslim students to be as gender related as did Agirdag, Loobuyck, and van Houtte () in their study of Flemish teachers. Even though attitudes to minorities have often been found to be gender related, in Finland this link seems to be weaker (see also Ketola ).…”
Section: Discussioncontrasting
confidence: 95%
“…However, the most important factor explaining teachers’ conceptions of whether integration is promoted in Finnish schools was the level at which they taught: upper secondary and adult education teachers were considerably less likely to make that claim than elementary and early education teachers or lower secondary school teachers. Agirdag, Loobuyck, and van Houtte () found that teachers in secondary schools have more negative attitudes to Muslim students than elementary education teachers. Interestingly, in our data this tendency is reversed: elementary and early education teachers had the most negative attitudes to Muslims and to their likelihood of integrating.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most live in the poorer districts of large and medium size cities and have rates of unemployment three to four times higher than the indigenous populations. Further, schools in Flanders, like schools elsewhere in Europe, reinforce these inequalities through a variety of selective mechanisms, including tracking structures, disciplinary procedures, and teacher expectations and recommendations (Agirdag, Loobuyck, & Van Houtte, 2012;Boone, 2013). This is reflected in lower-than-average performance levels, more frequent grade retention, overrepresentation in special education and lower secondary tracks, and higher dropout rates during secondary education (Clycq, Nouwen, & Vandenbroucke, 2014;Van Praag, 2013).…”
Section: Current Study: Purpose and Contextmentioning
confidence: 99%